Association Between Prekallikrein and Stroke: A Mendelian Randomization Study - Wang, Yinan; Jia, Yiming; Xu, Qingyun; Yang, Pinni; Sun, Lulu; Liu, Yi; Chang, Xinyue; He, Yu; Shi, Mengyao; Guo, Daoxia; Zhang, Yonghong; Zhu, Zhengbao (Journal of the American Heart Association, 2023)
Background High plasma prekallikrein was reported to be associated with increased risks of stroke, but the causality for these associations remains unclear. We aimed to investigate the associations of genetically predicted plasma prekallikrein concentrations with all-cause stroke, ischemic stroke, 3 ischemic stroke subtypes, and intracerebral hemorrhage (ICH) using a 2-sample Mendelian randomization approach. Methods and Results Seven independent prekallikrein-related single-nucleotide polymorphisms were identified as genetic instruments for prekallikrein based on a genome-wide association study with 1000 European individuals. The summary statistics for all-cause stroke, ischemic stroke, and ischemic stroke subtypes were obtained from the Multiancestry Genome-wide Association Study of Stroke Consortium with 40 585 cases and 406 111 controls of European ancestry. The summary statistics for ICH were obtained from the ISGC (International Stroke Genetics Consortium) with 1545 ICH cases and 1481 controls of European ancestry. In the main analysis, the inverse-variance weighted method was applied to estimate the associations of plasma prekallikrein concentrations with all-cause stroke, ischemic stroke, ischemic stroke subtypes, and ICH. Genetically predicted high plasma prekallikrein levels were significantly associated with elevated risks of all-cause stroke (odds ratio [OR] per SD increase, 1.04 [95% CI, 1.02-1.06]; =5.44×10 ), ischemic stroke (OR per SD increase, 1.05 [95% CI, 1.03-1.07]; =1.42×10 ), cardioembolic stroke (OR per SD increase, 1.08 [95% CI, 1.03-1.12]; =3.75×10 ), and small vessel stroke (OR per SD increase, 1.11 [95% CI, 1.06-1.17]; =3.02×10 ). However, no significant associations were observed for genetically predicted prekallikrein concentrations with large artery stroke and ICH. Conclusions This Mendelian randomization study found that genetically predicted high plasma prekallikrein concentrations were associated with increased risks of all-cause stroke, ischemic stroke, cardioembolic stroke, and small vessel stroke, indicating that prekallikrein might have a critical role in the development of stroke.